Prognostic value of circulating glypican-4 in chronic heart failure - Nora Schwegel; Viktoria Höller; Viktoria Santner; David Kajetan Zach; Jakob Lugitsch; Axel Muendlein; Eva Maria Brandtner; Andreas Leiherer; Heinz Drexel; Arthur Mader; Andrea Borenich; Stefan Pilz; et al. (Journal of Molecular Medicine, 2026)
Glypican-4 (GPC-4), an endothelial cell surface protein, is released into the circulation in the context of ischemia, inflammation, neurohumoral activity, and shear stress. This study aimed to investigate the prognostic value of GPC-4 in chronic heart failure. GPC-4 concentrations were determined in two prospective cohorts: patients with chronic heart failure with reduced ejection fraction (HFrEF), and with transthyretin amyloid cardiomyopathy (ATTR-CM). Multivariable Cox regression analyses were adjusted for age, sex, estimated glomerular filtration rate, N-terminal B-type natriuretic peptide, and left ventricular ejection fraction. In HFrEF ( n = 205, median age 66 years, 22% women), 58 patients (28%) died, 18 (9%) from cardiovascular cause, and 46 patients (22%) were hospitalized for worsening heart failure (WHF) during 4.2 years follow-up. In ATTR-CM ( n = 121, median age 76 years, 12% women), 34 patients (28%) died, 12 (10%) from cardiovascular cause, and 32 patients (26%) had a WHF hospitalization during 2.2 years follow-up. Baseline GPC-4 (median [interquartile range]) levels were 1553 (1041, 1950) pg/ml in HFrEF, and 2071 (1579, 2893) pg/mL in ATTR-CM. In HFrEF, GPC-4 was independently associated with all-cause mortality (HR 1.69, 95%CI 1.22–2.32, p = 0.003) and cardiovascular mortality (HR 1.61, 95%CI 1.01–2.56, p = 0.045), but not with WHF hospitalizations. Conclusively, in ATTR-CM, GPC-4 independently predicted all-cause mortality (HR 1.96, 95%CI 1.12–3.44, p = 0.018), but not cardiovascular mortality and WHF hospitalizations. GPC-4 carries strong prognostic value for all-cause death in chronic heart failure across various etiologies, but not for heart-failure specific outcomes. Further studies are warranted to elucidate its value in cardiovascular disease. Key messages Glypican-4 rises with ischemia, inflammation, neurohumoral activity, and shear stress. Circulating glypican-4 predicts prognosis in chronic heart failure, regardless of cause. Glypican-4 predicted all-cause death in heart failure with reduced ejection fraction and restrictive cardiomyopathy, but not heart failure–specific outcomes.

Leucine-rich α-2 glycoprotein 1 is associated with increased mortality risk in patients with peripheral artery disease - Axel Muendlein; Andreas Leiherer; Eva Maria Brandtner; Christine Heinzle; Kathrin Geiger; Stella Gaenger; Laura Schnetzer; Andreas Festa; Christoph H. Saely; Heinz Drexel (Journal of Molecular Medicine, 2025)

Myricetin attenuates hypoxia-induced inflammation in human adipocytes - Kathrin Geiger; Axel Muendlein; Andreas Leiherer; Stella Gaenger; Eva Maria Brandtner; Martin Wabitsch; Peter Fraunberger; Heinz Drexel; Christine Heinzle (Molecular Biology Reports, 2023)

Real-time PCR based detection of the lactase non-persistence associated genetic variant LCT-13910C>T directly from whole blood - Axel Muendlein; Andreas Leiherer; Christina Zach; Eva Maria Brandtner; Peter Fraunberger; Heinz Drexel; Kathrin Geiger (Molecular Biology Reports, 2019)